Strong emission of THz radiation from GaAs microstructures on Si - Inhee Maeng; Gyuseok Lee; Chul Kang; Gun Wu Ju; Kwangwook Park; Seoung-Bum Son; Yong-Tak Lee; Chul-Sik Kee (AIP Advances, 2018)
Remarkably strong emission of terahertz radiation from illuminated GaAs microstructures on a Si substrate is reported. The peak–to–peak amplitude of terahertz radiation from the sample is 9 times larger than that of THz radiation from a semi-insulating GaAs wafer. The spectral width of the sample is larger than that of a semi-insulating GaAs wafer; in particular, the spectral amplitude increases at higher frequencies. The presented GaAs microstructures on a Si substrate can be suitable for practical and efficient THz sources required in various THz applications.